Making CLIL workable. A review of Ball, P.; Kelly, K. and Clegg, J. (2015) Putting CLIL into Practice. - Fernández Fernández, Raquel (Pulso. Revista de educación, 2016)
Review of the book: Ball, P., Kelly, K. P., & Clegg, J. (2015). Putting CLIL into practice. Oxford University Press.